PENDAMPINGAN PEMAHAMAN FENOMENA PERNIKAHAN BEDA AGAMA PADA QS. AL-MAI’DAH: 5 DI HIMPUNAN MAHASISWA YAYASAN AL-KAHFI - Kholilurrohman, Kholilurrohman; Apinda , Lita; Nasirin, Nasirin; Lubis, Zakaria Husin; Firmansyah , Jun; Rahim , Abd. (MPP: Lembaga Penelitian Dan Studi Kebijakan, 2025)
This article discusses the phenomenon of interfaith marriage which is currently gaining popularity in Indonesia and invites pros and cons in society. In the perspective of Al-Qur'an interpretation, the author chooses to refer to two famous Indonesian commentators, namely Buya Hamka and M. Quraish Shihab. Both are figures of the modern-contemporary era in the field of interpretation, so their opinions are relevant to the current situation in Indonesia. In the interpretation of the Qur'an, the two commentators above interpret the QS. Al-Ma'idah [5]: 5 by prioritizing a spirit of tolerance and criticism of interfaith marriages. Even though there are constitutional arguments that regulate whether a marriage is valid or not based on the laws of each religious belief, facts on the ground prove that interfaith marriages still often occur in Indonesia. Thus, this research invites readers to understand more deeply the phenomenon of interfaith marriage through the lens of Al-Qur'an interpretation and Abdullah Saeed's approach. Hopefully this research will provide broader insight and understanding regarding the phenomenon of interfaith marriages in Indonesia